Urinary Tract Infections among Indonesian Pregnant Women and Its Susceptibility Pattern. (21st April 2020) - Rosana, Yeva; Ocviyanti, Dwiana; Halim, Melissa; Harlinda, Friza Yossy; Amran, Rahmah; Akbar, Wafridha; Billy, Matthew; Akhmad, Syadza Rhizky Putri
Abstract : Pregnant women are usually at risk of urinary tract infections (UTIs) such as asymptomatic bacteriuria. In the current multidrug-resistance era, appropriate diagnosis and treatment should be provided to avoid complications in pregnant women in developing countries, which have limited facilities, such as Indonesia. The aim of this study was to evaluate in vitro susceptibility tests. Urinary isolates were collected from 715 pregnant women who visited eight Community Health Centers in Jakarta, Indonesia, between 2015 and 2017. We identified bacterial uropathogens from samples that were positive for nitrite/leukocyte esterase (LE), using two types of VITEK cards. Since noncompliance among patients is a major problem, fosfomycin-trometamol 3 g single-dose sachets were given to the patients, and the side effects of the medication and neonatal outcomes were reported. Asymptomatic bacteriuria was found in 10.5% of the 715 pregnant women. Escherichia coli was the most common etiological factor (26.7%), followed by Klebsiella pneumoniae (20%), Streptococcus agalactiae (9.3%), Enterobacter cloacae (5.3%), Enterococcus faecalis (5.3%), Staphylococcus saprophyticus (4%), Acinetobacter baumannii (4%), and others . Out of 76 pregnant women who took fosfomycin-trometamol, two complained of diarrhea that subsided without medication and fever that responded to paracetamol. Neonatal outcomes showed 100% full-term and normal-weight babies. E. coli, including extended-spectrum beta-lactamase- (ESBL-) producing E. coli, was 100% susceptible to fosfomycin. Nitrite/LE test results are often used as evidence for empiric antibiotic administration for treating asymptomatic bacteriuria in pregnancy, but the diagnosis should be confirmed using culture tests. Based on in vitro susceptibility patterns and medication outcomes, fosfomycin-trometamol single dose could be administered to noncompliant UTI patients, including pregnant women.